2008
DOI: 10.1104/pp.108.128108
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Proliferating Arabidopsis Endosperm Reveals Biological Implications for the Control of Syncytial Division, Cytokinin Signaling, and Gene Expression Regulation    

Abstract: During the early stages of seed development, Arabidopsis (Arabidopsis thaliana) endosperm is syncytial and proliferates rapidly through repeated rounds of mitosis without cytokinesis. This stage of endosperm development is important in determining final seed size and is a model for studying aspects of cellular and molecular biology, such as the cell cycle and genomic imprinting. However, the small size of the Arabidopsis seed makes high-throughput molecular analysis of the early endosperm technically difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
115
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 113 publications
9
115
1
Order By: Relevance
“…The high level of cytokinin activity found in endosperm suggested that the plant hormone cytokinin regulates growth of seed components and controls seed mass or yield (53)(54)(55). More specifically, syncytial endosperm produces high amounts of cytokinin in many plant species such as coconut, maize, and rice (36,54,56,57).…”
Section: Discussionmentioning
confidence: 99%
“…The high level of cytokinin activity found in endosperm suggested that the plant hormone cytokinin regulates growth of seed components and controls seed mass or yield (53)(54)(55). More specifically, syncytial endosperm produces high amounts of cytokinin in many plant species such as coconut, maize, and rice (36,54,56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few of these studies, however, have focused exclusively on seeds and/or embryos to identify important regulators and processes required for seed development (27)(28)(29)(30)(31). In this paper, we present results of Affymetrix GeneChip experiments that profile genes that are active before, during, and after Arabidopsis seed formation.…”
mentioning
confidence: 99%
“…A first difficulty encountered in the characterization of MADS box type I members was their very low expression level. Preliminary analyses indicated that Ma and Mg subclasses are predominantly expressed in the inflorescences and siliques, and more meticulous studies using Affymetrix arrays showed that type I MADS box genes are expressed in male and female gametophytes as well as during early stage of endosperm and embryo development (Day et al, 2008;Walia et al, 2009;Tiwari et al, 2010;Wuest et al, 2010).The first Arabidopsis type I gene to be characterized functionally was AGL80/FEM111 (Portereiko et al, 2006), which belongs to the Mg subclade. AGL80/FEM111 is expressed in the central cell just before polar nuclei fusion, and in accordance with this observation, female gametophytes are severely affected in agl80/fem111 mutants (Schneitz et al, 1995;Christensen et al, 1997;Yadegari and Drews, 2004;Portereiko et al, 2006) (Figure 2,3).…”
mentioning
confidence: 99%